Energy cost and energy saving in distillation (rectification) of binary and ternary mixtures - M. K. Zakharov; A. A. Dovbish (Тонкие химические технологии, 2010)
Influence of difficulty of separation for energy cost in distillation and rectification was studied. It was shown that energy saving depends on reflux ratio